Prolonged Response to Aflibercept in Ovarian Cancer Relapse: A Case Report. Issue 1 (January 2015) - Redondo, Andrés; Castelo, Beatriz; Pinto, Alvaro; Zamora, Pilar; Espinosa, Enrique
VEGF-targeted therapies have shown activity in ovarian cancer, and one of them, bevacizumab, has been recently approved in this disease. Aflibercept is an antiangiogenic soluble fusion protein that inhibits VEGF-mediated signaling. In ovarian cancer, phase II trials with aflibercept have shown a significant benefit in the control of malignant ascites but with a lower response rate than expected. We report the case of a patient with relapsed ovarian cancer treated with aflibercept in fourth line, who experienced a prolonged response during more than two years with good tolerance. The duration of response to aflibercept was longer than that of the three previous lines of therapy (including the initial carboplatin-paclitaxel regimen) and ascites did not reappear. Further clinical research with this drug in ovarian cancer to identify patients who benefit most is warranted.